Space Radiation and Astronaut Safety - Seedhouse, Erik (SpringerBriefs in Space Development,, 2018)
This brief explores the biological effects of long-term radiation on astronauts in deep space. As missions progress beyond Earth's orbit and away from the protection of its magnetic shielding, astronauts risk constant exposure to higher levels of galactic cosmic rays and solar particle events. The text concisely addresses the full spectrum of biomedical consequences from exposure to space radiation and goes on to present possible ways to mitigate such dangers and protect astronauts within the limitations of existing technologies.